Extent of central neck dissection among thyroid cancer surgeons: Cross‐sectional analysis. (26th May 2015) - Deutschmann, Michael W.; Chin‐Lenn, Laura; Au, Jennifer; Brilz, Alan; Nakoneshny, Steve; Dort, Joseph C.; Pasieka, Janice L.; Chandarana, Shamir P.
ABSTRACT: Background: It is unclear if surgeons are performing comprehensive central neck dissections for well‐differentiated thyroid cancer. The purpose of this study was to determine mean lymph node retrieval in central neck dissection as well as variability across surgeons and institutions. Methods: A prospectively collected database identified 18 surgeons performing 425 central neck dissections, 313 unilateral and 112 bilateral. Demographics, perioperative, and pathologic factors were analyzed. Results: Mean lymph node yield was 7.4 and 11.9 for unilateral and bilateral central neck dissection, respectively. Although 224 central neck dissections were prophylactic, both total and pathologic lymph node yields were significantly higher in therapeutic central neck dissection. There was a significant variation in lymph node yield across individual surgeons, institutions, and regions. High‐volume central neck dissection surgeons have significantly lower lymph node yield compared to low‐volume surgeons. Conclusion: Central neck dissection seems to be performed adequately; however, there is a significant variation in lymph node yield. Future initiatives should try to standardize the central neck dissections performed, with emphasis on obtaining a sufficient yield. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E328–E332, 2016